Targeted gene silencing in mouse germ cells by insertion of a homologous DNA into a piRNA generating locus - Yamamoto, Yasuhiro; Watanabe, Toshiaki; Hoki, Yuko; Shirane, Kenjiro; Li, Yufeng; Ichiiyanagi, Kenji; Kuramochi-Miyagawa, Satomi; Toyoda, Atsushi; Fujiyama, Asao; Oginuma, Masayuki; Suzuki, Hitomi; Sado, Takashi; et al.

(untitled) (Genome Research, 2013)
In germ cells, early embryos, and stem cells of animals, PIWI-interacting RNAs (piRNAs) have an important role in silencing retrotransposons, which are vicious genomic parasites, through transcriptional and post-transcriptional mechanisms. To examine whether the piRNA pathway can be used to silence genes of interest in germ cells, we have generated knock-in mice in which a foreign DNA fragment was inserted into a region generating pachytene piRNAs. The knock-in sequence was transcribed, and the resulting RNA was processed to yield piRNAs in postnatal testes. When reporter genes possessing a sequence complementary to portions of the knock-in sequence were introduced, they were greatly repressed after the time of pachytene piRNA generation. This repression mainly occurred at the post-transcriptional level, as degradation of the reporter RNAs was accelerated. Our results show that the piRNA pathway can be used as a tool for sequence-specific gene silencing in germ cells and support the idea that the piRNA generating regions serve as traps for retrotransposons, enabling the host cell to generate piRNAs against active retrotransposons.